2016
DOI: 10.18632/oncotarget.13663
|View full text |Cite
|
Sign up to set email alerts
|

Association between XRCC1 polymorphisms and the risk of cervical cancer: a meta-analysis based on 4895 subjects

Abstract: The present meta-analysis was intended to explore the relationship between the X-ray repair cross complementing 1 (XRCC1) polymorphisms (Arg194Trp, Arg280His and Arg399Gln) and cervical cancer risk. Several electronic databases were searched systematically and bibliographies of relevant papers were identified carefully. Then, a meta-analysis was performed based on eligible studies in various genetic models. Pooled odds ratios (OR) with 95% confidence intervals (95% CI) were employed to evaluate the strength of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
2
14
0
2
Order By: Relevance
“…29 On the other hand, in a more recent report showed a weak association of XRCC1 gene in development of CC, however two studies by Zeng et al and Cai et al reported no evidence of association of XRCC genes with CC development. 31,32 Thus, there is a debate between association or no association between XRCC1 gene and risk of development of CC. Also, reports on XRCC2 Arg188His polymorphisms stated that XRCC2 variants were found not to be associated with CC risk.…”
Section: Discussionmentioning
confidence: 99%
“…29 On the other hand, in a more recent report showed a weak association of XRCC1 gene in development of CC, however two studies by Zeng et al and Cai et al reported no evidence of association of XRCC genes with CC development. 31,32 Thus, there is a debate between association or no association between XRCC1 gene and risk of development of CC. Also, reports on XRCC2 Arg188His polymorphisms stated that XRCC2 variants were found not to be associated with CC risk.…”
Section: Discussionmentioning
confidence: 99%
“…These differences suggest a possible ethnic variability in allele distribution of XRCC1 [44]. Another study analyzed 1,635 patients with cervical cancer and 2,361 controls, showing that the Arg399Gln polymorphism decreases the susceptibility of such cancer (G vs. A: OR = 0.39, CI of 95% = 0.29-0.51; p < 0.05) [45]. In a meta-analysis in the Caucasian populations, it was found that the A/G and G/G genotypes were associated with the risk of developing lung cancer [46].…”
Section: Discussionmentioning
confidence: 99%
“…6 XRCC1 memiliki tiga SNPs umum, varian genetik dalam XRCC1 adalah (C/T) dalam ekson 6 menghasilkan substitusi Arg / Trp pada kodon 194, (G/A) dalam ekson 9 mengubah asam amino Arg / His pada kodon 280 dan polimorfisme lain (G/A) dalam ekson 10 mengubah asam amino Arg / Gln pada kodon 399 pada stabilitas genomik. 6,7,8 Penelitian yang dilakukan pada populasi Asia menunjukkan hubungan yang signifikan antara polimorfisme XRCC1 Arg399Gln dan risiko karsinoma serviks. 9 Polimorfisme genetik adalah adanya variasi genetik pada suatu populasi dengan frekuensi lebih dari satu persen.…”
Section: Pendahuluanunclassified
“…XRCC1 telah dikaitkan dengan pengembangan karsinoma sel skuamosa esofagus, kanker serviks, kanker paru-paru, kanker pankreas, kanker payudara, kanker kolorektal, dan kanker lambung. 7 Kajian tentang polimorfisme gen XRCC1 Arg399Gln telah banyak dilakukan oleh berbagai peneliti dan di negara lain dan menghasilkan hasil yang bervariasi. Liu, dkk (2015) Dalam analisis subkelompok oleh etnis menunjukkan hubungan yang signifikan antara polimorfisme XRCC1 Arg399Gln dan kerentanan terhadap karsinoma serviks pada populasi Kaukasia dan Asia.…”
Section: Pendahuluanunclassified